Synthesis and Application of an Enantiomerically Pure Triflate Analogue of Microbially Derived 3-Halo-cis-1,2-dihydrocatechol Acetonides - Sun, Fenglai; Metz, Peter (Synlett, 2013)
(1S,2S)-3-Trifloxy-cis-1,2-dihydrocatechol acetonide, a useful chiral building block, was prepared from d-ribose in good overall yield using a carbonyl allylation and a ring-closing metathesis as the key C–C bond-forming steps. Negishi cross-coupling of this triflate with a serine-derived organozinc iodide proceeded efficiently to afford an α-amino acid derivative as a potential precursor for scabrosin esters (ambewelamides).
Keywords: chiral pool; allylation; metathesis; cross-coupling; scabrosin esters